Dialog Agama, Adat, dan Kebangsaan dalam Labuhan Sesaji Pantai Serang Blitar - Maknun, Moch. Lukluil; Nur Awalin, Fatkur Rohman; Rahmah, Yulinar Aini (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
This study of the Labuhan offerings tradition at Serang Beach, Blitar is focused on revealing the harmonization meaning of Javanese culture, religion, and national values in the Labuhan text. Revealing the potential for harmonization of Javanese culture, religion and national values in the Labuhan text is important as a big capital in realizing a moderate nation. By utilizing the methodological principles of oral tradition, and text hermeneutics, this study seeks to reveal the meaning of the harmony of the three elements. The results of the study show that the Labuhan Sesaji tradition can strengthen the identity of citizens as Javanese with culture, knowing their origins, and how to respond to foreign cultures in order to create a harmonious life. Religious nuances can also be seen from the texts of prayers and intentions that are read in the harbor procession.